Propuesta pedagógica para la formación humana : rememoración a través de textos audiovisuales - Ardila García, Diego Leonardo (Universidad de La Salle. Facultad de Ciencias de la Educación. Licenciatura en Lengua Castellana, Inglés y Francés (Lenguas Modernas)., 2017)
The actual article carried out during the period of the years 2014-2015, presents the Holocaust as an excuse for human development for students from grade 9th, 10th and 11th from the different educational institutions. Through audiovisual media, it made an intervention for achieving political subject development and historical memory; bearing in mind that the Peace Teaching and the resistance pedagogy suggested by Mantegazza as a backup. Based on the humanist pedagogy and critical pedagogy, the aim is to accomplish this education and with this article it is expected that the learning will go beyond the classroom towards the Colombian context and it will permit the subject to reassert his identity and freedom.